Utilization of imaging for severe injuries at the Beijing 2022 Winter Olympic Games - Drury, A.; Engebretsen, L.; Steffen, K.; Soligard, T.; Liu, R.; Forster, B. B. (Canadian Association of Radiologists Journal, 2024)
Purpose: In order to better understand the imaging of severe trauma in sport, this study describes the imaging modalities utilized to image athletes who experienced severe traumatic injuries at the Beijing Winter Olympic Games 2022, the distribution of these modalities in relation to the sporting facilities, and the types of injuries imaged in each sport.